Analysis of known amyotrophic lateral sclerosis and frontotemporal dementia genes reveals a substantial genetic burden in patients manifesting both diseases not carrying the C9orf72 expansion mutation. Issue 2 (9th September 2017) - Dols-Icardo, Oriol; García-Redondo, Alberto; Rojas-García, Ricardo; Borrego-Hernández, Daniel; Illán-Gala, Ignacio; Muñoz-Blanco, José Luís; Rábano, Alberto; Cervera-Carles, Laura; Juárez-Rufián, Alexandra; Spataro, Nino; De Luna, Noemí; Galán, Lucía; et al.
Abstract : Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are part of a clinical, pathological and genetic continuum. Objectives: The purpose of the present study was to assess the mutation burden that is present in patients with concurrent ALS and FTD (ALS/FTD) not carrying the chromosome 9 open reading frame 72 ( C9orf72 ) hexanucleotide repeat expansion, the most important genetic cause in both diseases. Methods: From an initial group of 973 patients with ALS, we retrospectively selected those patients fulfilling diagnostic criteria of concomitant ALS and FTD lacking the repeat expansion mutation in C9orf72 . Our final study group consisted of 54 patients clinically diagnosed with ALS/FTD (16 with available postmortem neuropathological diagnosis). Data from whole exome sequencing were used to screen for mutations in known ALS and/or FTD genes. Results: We identified 11 patients carrying a probable pathogenic mutation, representing an overall mutation frequency of 20.4%. TBK1 was the most important genetic cause of ALS/FTD (n=5; 9.3%). The second most common mutated gene was SQSTM1, with three mutation carriers (one of them also harboured a TBK1 mutation). We also detected probable pathogenic genetic alterations in TAF15, VCP and TARDBP and possible pathogenic mutations in FIG4 and ERBB4 . Conclusion: Our results indicate a high genetic burden underlying the co-occurrence of ALS and FTD and expand the phenotype associated with TAF15, FIG4 and ERBB4 to FTD. A systematic screening of ALS and FTD genes could be indicated in patients manifesting both diseases without the C9orf72 expansion mutation, regardless of family history of disease.